Wave motion in elastic structures - Brennan, M. J. [UNESP]; Tang, B.; Almeida, F. C.L. [UNESP] (My University, 2016)
Describing the dynamic behaviour of structures in terms of waves is particularly useful when high frequency vibration is of interest. This is the case in active and passive vibration control, and in structural health monitoring. In this chapter, the concept of wave motion is introduced and different types of waves are discussed, namely waves in a string, a rod and a beam. Using the wavenumber, the phenomenon of dispersion is introduced as is phase and group velocity, and cut-off. The emphasis is on the physical concepts rather than mathematics, and to this end, the majority of the chapter concentrates on one-dimensional uniform structures.
Keywords: Beams; Cut-off frequency; Dispersion; Group velocity; Phase velocity; Rods; Strings; Wave motion; Wavenumber